Analyse préliminaire et discussion sur la nature d’un dépôt dentaire très particulier - Yves Gleize; Dominique Castex; Rémy Chapoulie; Henri Duday (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
An unusual dental deposit characterizes a skeleton from the excavation of the medieval graveyard at Clarensac (Gard, France). Its large size led us to investigate its origin, but the results of macroscopic examination alone are inconclusive. It could be either a biological formation such as tartar or a taphonomic process. To further our investigation, we carried out an analysis of the atomic composition of the deposit using a scanning electron microscope (SEM). This revealed the presence of atoms which are constituents of the inorganic portion of tartar. However, a post mortem calcification on a tartar deposit which was already present cannot be excluded. The existence of another example in the anthropological series studied, although smaller, indicates the importance of the loss of antagonist teeth in the development of such deposits.